Fruit quality evaluation of plantains, plantain hybrids, and cooking bananas - Ferris, R.S.B.; Ortíz, R.; Vuylsteke, D.R. (1999)
Triploid plantains (Musa AAB) are among the most important horticultural crops of West Africa. However, all landraces are susceptible to black Sigatoka, a fungal disease caused by Mycosphaerella fijiensis, Morelet. To ameliorate the spread of this epidemic, exotic triploid cooking bananas (ABB), with resistance to black Sigatoka, were introduced into West Africa and new disease resistant polyploid Musa (AAAB) germplasm developed through conventional cross-breeding of French plantains (AAB). To ensure that released materials would compete with landraces on a fruit quality basis, an evaluation methodology was developed to compare exotic and hybrid Musa genotypes with West African triploid landraces. Tests showed that plantain hybrids and cooking bananas had heavier bunches than plantain landraces. The plantain hybrids generally produced more but smaller fruit compared with False Horn plantain (AAB). The fruit ripening time of plantain hybrids and the cooking banana cultivar Pelipita was longer than that of plantain landraces, and selected plantain hybrids had fruit with a dry matter content similar to that of the female parent. The fruit of ripe plantain landraces had a firmer texture than plantain hybrids and the landraces Agbagba and Bobby Tannap had lower levels of soluble solids at specific stages of ripening compared with the other Musa germplasm. These results showed that simple physical tests can be used to select for higher quality cooking bananas and plantain hybrids and that specific plantain hybrids, within the test group, showed a higher potential for market acceptance. © 1999 Published by Elsevier Science B.V. All rights reserved.